Jack goes west - Barnett, Mac; Pizzoli, Greg (New York : Viking, 2020)
Jack and the Lady take the train West to visit a dude ranch. One night, there's a bank robbery next door, and Jack is pegged as the bandit. But thanks to Jack's new rope tricks, the real robber is caught, and Jack leaves the Wild West a free rabbit with a big secret.
School Library Journal, December 2019
Horn Book, January 2020
Bulletin (Center for Children's Books), February 2020
Kirkus Review, November 2019
1.5
K-3
Keywords: Rabbits -- Juvenile fiction; Friendship -- Juvenile fiction; Bank robberies -- Juvenile fiction; Brigands and robbers -- Juvenile fiction; Rabbits -- Fiction; Friendship -- Fiction; Bank robberies -- Fiction; Robbers and outlaws -- Fiction; Readers (Elementary)